2015
DOI: 10.1182/blood.v126.23.832.832
|View full text |Cite
|
Sign up to set email alerts
|

The BTK Inhibitor, Bgb-3111, Is Safe, Tolerable, and Highly Active in Patients with Relapsed/ Refractory B-Cell Malignancies: Initial Report of a Phase 1 First-in-Human Trial

Abstract: Introduction: Bruton's tyrosine kinase (BTK) is a downstream intermediary of B cell receptor (BCR) signaling. As revealed by ibrutinib, disruption of BCR signaling results in significant anti-tumor activity in various B cell malignancies. BGB-3111 is a potent, specific and irreversible BTK inhibitor. In biochemical and cellular assays, BGB-3111 was more selective than ibrutinib for BTK vs. EGFR, FGR, FRK, HER2, HER4, ITK, JAK3, LCK, BLK and TEC. Activity against these other kinases is implicated in ibrutinib-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 0 publications
1
69
0
Order By: Relevance
“…More encouraging response rates have been seen in a Phase I trial of ONO/GS-4059, in which 24 of 25 evaluable CLL patients (96%) responded [33]. Similarly, with BGB-3111, an ORR in CLL of 93% (13/14 patients) was reported [34]. However, data on PFS and response duration are not yet available.…”
Section: Other Btk Inhibitors In Cllmentioning
confidence: 96%
“…More encouraging response rates have been seen in a Phase I trial of ONO/GS-4059, in which 24 of 25 evaluable CLL patients (96%) responded [33]. Similarly, with BGB-3111, an ORR in CLL of 93% (13/14 patients) was reported [34]. However, data on PFS and response duration are not yet available.…”
Section: Other Btk Inhibitors In Cllmentioning
confidence: 96%
“…Zanubrutinib (BGB-3111) is an investigational, highly specific, next-generation BTK inhibitor that has demonstrated encouraging clinical activity in phase 1/2 studies [14][15][16][17] and is currently in phase 3 testing for multiple indications [18][19][20]. In patients with B-cell malignancies, zanubrutinib was generally well tolerated at total daily doses ranging from 40 to 320 mg, and the recommended phase 2 dose is 160 mg administered twice daily [16]. Pharmacokinetic (PK) data showed that zanubrutinib was rapidly absorbed after oral administration, with C max observed at Electronic supplementary material The online version of this article (https ://doi.org/10.1007/s0028 0-019-04015 -w) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Additional selective BTK inhibitors, such as ONO/GS-4059 (Walter et al, 2016) and BGB-3111a (Tam et al, 2015), are under clinical development, thereby expanding the potential therapeutic options for B cell malignancies.…”
Section: Second-generation Btk Inhibitorsmentioning
confidence: 99%